2006
DOI: 10.1177/026119290603400508
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Impedance-based Sensors for Cell Adhesion Monitoring andIn VitroMethods for Detecting Cytotoxicity Induced by Chemicals

Abstract: The recent European Commission REACH (Registration, Evaluation and Authorisation of Chemicals) policy outlines a plan for toxicological testing by using alternative non-animal in vitro methods. In this context, there is a need to develop and standardise high-throughput screening (HTS) methods for studying the cytotoxicity induced by chemicals. Electrochemical impedance spectroscopy (EIS) can be considered as a complementary technique to alternative in vitro testing for studying cell adhesion to the substrate, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 22 publications
(46 reference statements)
1
6
0
Order By: Relevance
“…It has been reported that cytotoxicity not only depends on the physicochemical properties of particles, but also varies with the cellular type investigated [22]. Therefore, even if our results are in contrast to other studies performed using different cell lines and different silica NPs, we are confident of the reliability and reproducibility of the CFE assay for testing NPs [49,54].…”
Section: Discussionmentioning
confidence: 43%
“…It has been reported that cytotoxicity not only depends on the physicochemical properties of particles, but also varies with the cellular type investigated [22]. Therefore, even if our results are in contrast to other studies performed using different cell lines and different silica NPs, we are confident of the reliability and reproducibility of the CFE assay for testing NPs [49,54].…”
Section: Discussionmentioning
confidence: 43%
“…In fact the cytome assay measures the frequency of cell division and the evaluation occurs directly after the end of the NP exposure. On the contrary, the CFE assay does not refer to a specific mechanism of cytotoxicity, and colonies can origin from any surviving cell following 7 days of culture and after 4 days by the end of the exposure period (20). Taken together these data suggest that ZrO 2 NP are able to induce cell death, however cells not too heavily damaged remain viable, continue to replicate themselves and are able to form colonies.…”
Section: Discussionmentioning
confidence: 96%
“…The results were consistent with findings from the traditional MTT assay. 105 In summary, impedance-based methods for cytotoxicity testing are simple, cost-effective, labelfree, lend themselves to HTS, and importantly allow in situ monitoring of not just cytotoxicity but also other aspects of cell physiology such as proliferation, morphology, attachment, and intercellular adhesion. These methods are widely used in pharmaceutical research, oncology, cardiology, and other fields of biomedicine and clinical research, to investigate responses of cells to exposure to bioactive chemical agents and toxicants.…”
Section: Impedance-based Monitoringmentioning
confidence: 99%